The repA Gene of the Linear Yersinia enterocolitica Prophage PY54 Functions as a Circular Minimal Replicon in Escherichia coli - Ziegelin, Günter (American Society for Microbiology, 2005)
The Yersinia enterocolitica prophage PY54 replicates as a linear DNA molecule with covalently closed ends. For replication of a circular PY54 minimal replicon that has been derived from a linear minireplicon, two phage-encoded loci are essential in Escherichia coli: (i) the reading frame of the replication initiation gene repA and (ii) its 212-bp origin located within the 3′ portion of repA. The RepA protein acts in trans on the origin since we have physically separated the PY54 origin and repA onto a two-plasmid origin test system. For this trans action, the repA 3′ end carrying the origin is dispensable. Mutagenesis by alanine scan demonstrated that the motifs for primase and for nucleotide binding present in the protein are essential for RepA activity. The replication initiation functions of RepA are replicon specific. The replication initiation proteins DnaA, DnaG, and DnaB of the host are unable to promote origin replication in the presence of mutant RepA proteins that carry single residue exchanges in these motifs. The proposed origins of the known related hairpin prophages PY54, N15, and PKO2 are all located toward the 3′ end of the corresponding repA genes, where several structure elements are conserved. Origin function depends on the integrity of these elements.